Nursing Roles and Clinical Considerations in the Induction of Labor - Alotibi, Fahad Abdullah Nasir; Khulud Abdullah Aldosseri,; Abrar Yousef Banibakhsh,; Raed Ibrahim Ismail Mawkili,; Wejdan Ibrahim Alaithan,; Bander Hussan Almutery,; Abdulrahman Almutairi,; MUQRIN KHALAF ALMUTAIRI,; Heassa Saleh Saad Alhumaidy,; Woroud Jarallah Mualla Alreshidi,; ADEL KHALID SAAD ALHARBI,; Shatha Ali Albargi, (Saudi Journal of Medicine and Public Health, 2025)
Background: Induction of labor is a common obstetric intervention used to initiate uterine contractions when continuation of pregnancy poses greater maternal or fetal risk than delivery. Its global use has increased substantially, requiring safe, evidencebased clinical practice and effective interprofessional collaboration. Aim: This article aims to review the clinical considerations of labor induction and highlight the essential nursing roles in ensuring maternal and fetal safety during the induction process. Methods: A narrative review of current obstetric guidelines, clinical trials, and systematic reviews was conducted to examine indications, contraindications, methods, complications, and nursing interventions related to induction of labor. Results: Induction of labor is indicated for various maternal and fetal conditions such as hypertensive disorders, diabetes, fetal growth restriction, and postterm pregnancy. Mechanical and pharmacological methods are widely used, each with specific benefits and risks. Evidence demonstrates that appropriately managed induction does not increase cesarean section rates and may improve perinatal outcomes. Nurses play a pivotal role in assessment, medication administration, continuous fetal monitoring, early detection of complications, and patient education. Conclusion: Induction of labor is a complex yet essential obstetric intervention that requires comprehensive clinical assessment and skilled nursing care. Adherence to evidencebased protocols and effective teamwork is critical to optimizing outcomes.